A Queueing Approach in Determining Optimal Numberof Beds in a Hospital Serving Urgent and Non-Urgent Patients - Abolnikov, L.; Zachariah, T.M. (Электронное моделирование, 2010)
In this paper, the authors consider a hospital as a multichannel queueing system that serves two different arriving Poisson flows of urgent and non-urgent customers (patients). The distribution of the service time is assumed to be exponential with different parameters for each kind of patients and priority for urgent patients. The results of the article are illustrated by several numerical examples obtained with the help of Mathematica program and can be easily applied to any hospital or its department.